ANALISIS KETERAMPILAN PROSES SAINS MELALUI MODEL INKUIRI TERBIMBING BERBANTUAN LIVEWORKSHEET PADA MATERI GAYA SMP - Fania Nur Aulia Hidayah; Tutut Nurita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of a guided inquiry learning model assisted by Liveworksheet in improving students’ science process skills on the topic of force. This study employed a pre-experimental method with a one group pretest-posttest design. The research subjects consisted of 32 seventh-grade students. Data were collected through science process skills tests administered before (pretest) and after (posttest) the treatment. The results showed an improvement in students’ science process skills after the implementation of the guided inquiry learning model assisted by Liveworksheet. This was supported by the paired sample t-test result, which obtained a significance value of 0.000 (<0.05), indicating a significant difference between pretest and posttest scores. In addition, the N-Gain analysis showed an average value of 0.66, categorized as moderate. Improvement occurred across all indicators of science process skills, with the highest increase in drawing conclusions and the lowest in identifying variables. Therefore, it can be concluded that the implementation of the guided inquiry learning model assisted by Liveworksheet is effective in improving students’ science process skills on the topic of force.